Pembuktian Surat Dakwaan Mengenai Tindak Pidana Penghinaan (Pencemaran Nama Baik) yang Diatur dalam Pasal 310 Ayat 1 KUH Pidana Dihubungkan dengan Undang-Undang No. 40 Tahun 1999 Tentang Pers - Kusyana Kusyana (LPPM IAI Pangeran Dharma Kusuma Segeran Indramayu, 2025)
The law enforcement process is a continuous activity carried out by the apparatus (officers) according to the needs of the law, where law enforcement must be fair and impartial. The issue of law enforcement in Indonesia is a complex issue, where one is very closely related to another. The 1945 Constitution states that the Republic of Indonesia is a state of law, not a state of power. Defendant KSY, S.E. BIN GANI on Sunday, January 27, 2002 at approximately 10:00 WIB or at least at a certain time in January 2002, located in the Indramayu area or at least in another place that is still included in the jurisdiction of the District Court, intentionally attacked the honor or good name of another person, namely the victim witness SUBIYANTO BIN SUTARA. The act was carried out by disseminating the show openly or by attaching writing or pictures, to a civil servant during or in carrying out his duties legally, which act was carried out in the following manner: At the time and place as mentioned above, initially the Defendant from January 21, 2002 until he made a picture of the victim witness and a writing entitled